Understanding Institutional Life-Cycle and Sustainability of Co-operative Model: A Case Study of CAMPCO, India - Jyotishi, Amalendu; M.G., Deepika (The Indonesian Journal of Socio-Legal Studies, 2022)
Co-operative movement in India has a long-standing contribution in the growth of business, agriculture and allied activities. One such cooperative movement in India is the Central Arecanut and Cocoa Marketing and Processing Co-operative Limited (CAMPCO) which was initiated with a joint cooperation between the states of Karnataka and Kerala to create an organized market structure for the two plantation crops namely Arecanut and Cocoa in the backdrop of falling market price of these crops. CAMPCO is an interesting co-operative movement, worth investigating in terms of its evolution, challenges, growth and diversification. The paper tries to examine the factors responsible for justifying the existence of the Co-operative structure and its sustainability in the context of CAMPCO, using a modified cooperative life-cycle framework.